Вождь краснокожих: новеллы / О. Генри - Генри О. (Школьная программа по чтению, 2019)
Экземпляры: ф.16 (20210621) / Инвентарный номер: 61030 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Г 34 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44